Human-wildlife conflict and its impacts on livelihoods, health, and the environment in Chebera Churchura National Park, Southwest Ethiopia: a phenomenological study using a One Health approach with an urgent call for action - Guadu, T.; Berhane, A.; Solomon, T.; Tafese, A.; Tesfay, K.; Asgedom, A.A.; Abera, B.; Debebe, B.; Getachew, M.; Shibabaw, A.; Araba, A.; Abdurahman, M.; et al. (BioMed Central, 2026)
Background: Chebera Churchura National Park (CCNP), located in Southwest Ethiopia, was established to conserve biodiversity. However, its contribution to the livelihood and wellbeing of the proximal communities remains limited. Local people derive few tangible benefits from conservation while facing significant costs through crop losses, livestock predation, and restricted access to natural resources factors that intensify human-wildlife conflict (HWC). Previous studies have addressed HWCs focused mainly from ecological and socio-economic aspects with limited attention to the interlinked health dimensions of human, animals and ecosystems. This study aims to fill this gap by (i) examining the extent and effect of HWCs on livelihoods in CCNP, (ii) exploring community perceptions of wildlife and conservation, and ii) identifying participatory strategies for conflict mitigation through a One Health approach.